PEMBERDAYAAN MELALUI KETRAMPILAN KREATIF UNTUK MENGEMBANGKAN PENGETAHUAN DAN BAKAT ANAK PENYANDANG DISABILITAS DI MI 2 JOMBANG JEMBER - Ratnasari, Khurin In; Zaeni, Akhmad; Shalihah, Imra'atus; Hakim, Faisol; Bukhori, Imam; Mukhsin, Mukhsin (Pandalungan: Jurnal Pengabdian kepada Masyarakat, 2025)
Inclusive education provides equal opportunities for children with disabilities to develop according to their potential. However, in practice, many students with special needs still face various obstacles in the learning process, especially if only conventional methods are used. This research aims to empower children with disabilities at MI 2 Jombang, Jember, through creative skills as an innovative learning medium. The modelling method uses ABCD. The results show that creative skills are effective to improve academic understanding, motor skills, as well as self-confidence of children with disabilities. The implementation of this empowerment programme is done through the integration of creative skills in, teacher training, provision of supporting facilities, and cooperation. A creative skills-based approach can have a positive impact on the intellectual and emotional development of children with disabilities. Therefore, support from various parties, including schools, parents and communities, is needed to ensure the sustainability of this programme in improving the quality of inclusive education. Keywords: Inclusive education,creative skills, children with disabilities, empowerment